2013
DOI: 10.1097/aap.0b013e3182890d50
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Root/Trunk (Interscalene) Block for Hand and Forearm Anesthesia

Abstract: Background Historically, the anterolateral interscalene block—deposition of local anesthetic adjacent to the brachial plexus roots/trunks—has been used for surgical procedures involving the shoulder. The resulting block frequently failed to provide surgical anesthesia of the hand and forearm, even though the brachial plexus at this level included all of the axons of the upper extremity terminal nerves. However, it remains unknown whether deposition of local anesthetic adjacent to the seventh cervical root or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…17 In the present study, we observed incomplete sensory block in the median (43%), musculocutaneous (20%), radial (33%), and ulnar (78%) territories. Although this may appear surprising, Madison et al, 18 using an ISB insertion technique targeting the C7 root for anesthesia of the hand, found inadequate sensory block of the musculocutaneous nerve in 42% at 30 minutes using mepivacaine 1.5%.…”
Section: Discussionmentioning
confidence: 99%
“…17 In the present study, we observed incomplete sensory block in the median (43%), musculocutaneous (20%), radial (33%), and ulnar (78%) territories. Although this may appear surprising, Madison et al, 18 using an ISB insertion technique targeting the C7 root for anesthesia of the hand, found inadequate sensory block of the musculocutaneous nerve in 42% at 30 minutes using mepivacaine 1.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Our success rate in supraclavicular and infraclavicular groups was comparable to previous reports using US-guided nerve blocks 3,4,7 . Though the interscalene block has been found to be highly effective for shoulder surgery 11,12 , a high incidence of inadequate anaesthesia of the forearm and hand has been reported 20 . The high surgical effectiveness of interscalene blockade for arm and forearm surgery in our study may be due to the use of a different approach or choice of local anaesthetic type and volume.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning 30 min following Stimulator C initiation, subjects could receive intravenous fentanyl or hydromorphone prior to discharge and/or receive a single-injection interscalene nerve block (ropivacaine 0.5%, 20 mL, with epinephrine) 13. Subjects and their caretakers were provided verbal and written instructions on stimulator/lead care and management.…”
Section: Methodsmentioning
confidence: 99%